The relationship between nest location selection of Barn swallows (Hirundo rustica) and human activity and residence - Minyoung Kim; Ok-Sik Chung; Jong Koo Lee (Scientific Reports, 2023)
Abstract We found that barn swallow (Hirundo rustica) breeding occurs within close proximity to humans. An evaluation of barn swallow breeding frequency and the breeding success rate of swallows at research sites, which were buildings inhabited by humans and buildings where humans had previously resided, was conducted in order to establish a relationship between the location of barn swallow nests and human habitation and activity frequency. The results demonstrated that barn swallows often breed in human-inhabited buildings. No significant relationship was observed between the wall material and the direction of the wall and the type of building, whereas a much higher proportion of the nests were located near doors with a high level of human movement. In addition, no significant correlation was observed between the location of the nest and the distance from potential resources (food, water etc.), however, a statistically significant relationship was observed between the frequency of human activity measured through the video camera and the number of nests located at a certain distance. The average number of offspring and the reproductive success rate were higher in nests located within close proximity to human activity compared to nests not located within close proximity to human activity, suggesting that the presence of humans had a positive effect on reproduction. This study show that barn swallow nesting occurs in locations where there is a human influence and humans provide implicit protection of swallows from predation, which has a significant impact on breeding.